TRADUCTION DES EXPRESSIONS IMAGÉES EN FRANÇAIS ET LEUR IMPORTANCE LINGUOCULTURELLE (Modern education and development, 2025)
This article explores the translation of figurative expressions in French and their linguocultural significance. Through comparative analysis, it highlights the challenges of translating idioms, proverbs, and metaphors while preserving their cultural essence. Examples in French with English translations are provided to illustrate linguistic and cultural nuances.